2017
DOI: 10.14198/jhse.2017.122.09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of relationships between the use of visual display terminals, craniocervical angle and physical activity: A pilot study

Abstract: Grounds: The neck posture alterations can cause cervical pain and implicitly produce changes in the neck movement patterns, resulting in a greater risk of musculoskeletal disorders of the neck. The forward head position implies bending of the lower cervical spine and extension of the upper cervical spine. This is a common clinical observation in patients who have a sore neck and shoulders. The main objective of the study is to identify the relationship between the posture, the use of visual display units and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…The mean angular increase in NF was very small (1.3° with 30 min increased computer use over the one‐year period). Since increased NF resembles forward head posture (FHP), this underpins the theory that computer use and FHP are associated in the adult population (García‐Remeseiro & Gutiérrez‐Sánchez, 2017; Kang et al, 2012,), but not necessarily the source of, or the risk for, UQMP. However, this study found that adolescent computer users are at‐risk of developing UQMP when their NF angle changed into extension ≤−2.9° irrespective of from where in the range the participant moved.…”
Section: Discussionmentioning
confidence: 97%
“…The mean angular increase in NF was very small (1.3° with 30 min increased computer use over the one‐year period). Since increased NF resembles forward head posture (FHP), this underpins the theory that computer use and FHP are associated in the adult population (García‐Remeseiro & Gutiérrez‐Sánchez, 2017; Kang et al, 2012,), but not necessarily the source of, or the risk for, UQMP. However, this study found that adolescent computer users are at‐risk of developing UQMP when their NF angle changed into extension ≤−2.9° irrespective of from where in the range the participant moved.…”
Section: Discussionmentioning
confidence: 97%
“…La evaluadora era usuaria regular del software SAPO/PAS 22 . Las imágenes fueron calibradas según la distancia y la línea vertical.…”
Section: Procedimientounclassified